Safety and tolerability of autologous bone marrow mesenchymal stromal cells in ADPKD patients - Atieh Makhlough; Soroosh Shekarchian; Reza Moghadasali; Behzad Einollahi; Seyedeh Esmat Hosseini; Neda Jaroughi; Tina Bolurieh; Hossein Baharvand; Nasser Aghdami (Stem Cell Research & Therapy, 2017)
Abstract Background Autosomal dominant polycystic kidney disease (ADPKD) is a genetic ciliopathy disease characterized by progressive formation and enlargement of cysts in multiple organs. The kidneys are particularly affected and patients may eventually develop end-stage renal disease (ESRD). We hypothesize that bone marrow mesenchymal stromal cells (BMMSCs) are renotropic and may improve kidney function via anti-apoptotic, anti-fibrotic, and anti-inflammatory effects. In this study, we aim to assess the safety and tolerability of a BMMSC infusion in ADPKD patients. Methods We performed a single-arm phase I clinical trial with a 12-month follow-up. This study enrolled six eligible ADPKD patients with an estimated glomerular filtration rate (eGFR) of 25–60 ml/min/1.73 m2. Patients received autologous cultured BMMSCs (2 × 106 cells/kg) through the cubital vein according to our infusion protocol. We investigated safety issues and kidney function during the follow-up visits, and compared the findings to baseline and 1 year prior to the intervention. Results There were no patients lost to follow-up. We observed no cell-related adverse events (AE) and serious adverse events (SAE) after 12 months of follow-up. The mean eGFR value of 33.8 ± 5.3 ml/min/1.73 m2 1 year before cell infusion declined to 26.7 ± 3.1 ml/min/1.73 m2 at baseline (P = 0.03) and 25.8 ± 6.2 ml/min/1.73 m2 at the 12-month follow-up visit (P = 0.62). The mean serum creatinine (SCr) level of 2 ± 0.3 mg/dl 1 year before the infusion increased to 2.5 ± 0.4 mg/dl at baseline (P = 0.04) and 2.5 ± 0.6 mg/dl at the 12-month follow-up (P = 0.96). This indicated significant changes between the differences of these two periods (12 months before infusion to baseline, and 12 months after infusion to baseline) in SCr (P = 0.05), but not eGFR (P = 0.09). Conclusions This trial demonstrated the safety and tolerability of an intravenous transplantation of autologous BMMSCs. BMMSC efficacy in ADPKD patients should be investigated in a randomized placebo-controlled trial with a larger population, which we intend to perform. Trial registration ClinicalTrials.gov, NCT02166489 . Registered on June 14, 2014.